2022
DOI: 10.1021/acs.jpcc.2c00317
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Electrocatalytic Reduction and Sensing of Hazardous Hexavalent Chromium Using a Redox-Active Binol Species-Impregnated Carbon Nanofiber-Modified Electrode

Abstract: Electrochemical reduction of the hexavalent chromium compounds, a serious environmental pollutant and carcinogen, to a nontoxic Cr(III) species is of significant research interest in interdisciplinary areas. Due to its high oxidation potential (1.36 V vs RHE) and associated surface fouling problems with organic-electrocatalyst systems, expensive precious metalbased electrodes like Au, Ag, Pt, and Pd have been widely used for this purpose. Herein we report, an in situ electrochemically prepared highly redox-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…The result describes a symmetric energy barrier for the electron transfer reaction. The obtained k s value is comparable with that of redox-active hydroquinone derivative 30,31 and 1,10-phenanthroline-quinone 32 molecular system-immobilized carbon nanomaterialmodified electrodes. Furthermore, this new redox system showed a proton-coupled electron transfer characteristic (slope = −59 ± 3 mV dec −1 ) obeying the Nernstian mechanism with the participation of an equal number of protons and electrons in the electrochemical reaction (real value, −58 mV dec −1 ) (Figure 1E,F).…”
Section: Electrochemical Response Of Acetaminophen On the Gce/cb In N...supporting
confidence: 67%
“…The result describes a symmetric energy barrier for the electron transfer reaction. The obtained k s value is comparable with that of redox-active hydroquinone derivative 30,31 and 1,10-phenanthroline-quinone 32 molecular system-immobilized carbon nanomaterialmodified electrodes. Furthermore, this new redox system showed a proton-coupled electron transfer characteristic (slope = −59 ± 3 mV dec −1 ) obeying the Nernstian mechanism with the participation of an equal number of protons and electrons in the electrochemical reaction (real value, −58 mV dec −1 ) (Figure 1E,F).…”
Section: Electrochemical Response Of Acetaminophen On the Gce/cb In N...supporting
confidence: 67%
“…Plausibly, at highly bioelectrocatalytic spots, the local H 2 O 2 concentration within the gap between the substrate and the Pt-Tip is depleted, which leads to a marked Pt Tip current decrement over the substrate. Bioelectrocatalytic spots of different nature, activity, and inhomogeneities within the surface cause specific variations in the imaging current signals . Previously, our group has utilized this technique for analyzing the in situ formation of nickel hexacyanoferrate and molecular oxidation reactions. , Figure A is an illustration of the RC-SECM operational procedure, wherein simultaneous reduction of H 2 O 2 by the GCE/CB@NQ/Cytc (at open-circuit, Step-1) and the Pt Tip (Step-1′) has been explored.…”
Section: Resultsmentioning
confidence: 99%
“…Figure S5C Next, a redox-competition SECM (RC-SECM) technique was adopted in couple with an H 2 O 2 electrochemical reduction reaction as an in situ redox probe. 63 The variation in the kinetics of the H 2 O 2 reduction reaction between the substrate and the tip electrode was turned for the imaging. 63 If the Pt Tip position is in close proximity to an active electrocatalyst site, a marked decrement in the SECM-Tip current (imaging) will be noticed.…”
Section: Det Mechanism For the Bioelectrocatalytic Reduction Of H 2 Omentioning
confidence: 99%
See 1 more Smart Citation
“…The above experimental results demonstrated that hybrid 1 is a promising bifunctional PEC sensor for the detection of Cr(VI) and TC. [44][45][46] To gain more insights, the catalytic mechanisms of the electrocatalytic Cr(VI) reduction 47 and electrooxidation of TC 48 over hybrid 1 were investigated by the chronoamperometry technique. Fig.…”
Section: Photoelectrochemical Catalytic Mechanism Of Hybrid 1 For Cr(...mentioning
confidence: 99%